Community Service Data Visualization at PT Surya Data Infocreasi in Retail Companies X, Y and Z - Yosia; Januaviani, Trisha M.A (PT FORMOSA CENDEKIA GLOBAL, 2024)
This Community Service (PKM) is carried out at PT Surya Data Infokreasi with a focus on data visualization using the Power BI platform. This service aims to increase the efficiency of understanding customer data and the company's business performance. Design and implement interactive reports using various Power BI visualizations such as graphs, maps, and dynamic tables. Interactive slicers and filters are applied to give users flexibility in exploring data in greater depth or detail. The main focus of visualization is sales analysis, customer trends, and inventory monitoring. Selection of performance metrics including total sales, customer returns, and profit analysis. The implication of this service is to help facilitate understanding of data in terms of patterns, trends and information contained in the data.